2019
DOI: 10.1002/anie.201905578
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent GLUT Inhibitor from a Library of Rapafucins by Using 3D Microarrays

Abstract: Glucose transporters play an essential role in cancer cell proliferation and survival and have been pursued as promising cancer drug targets. Using microarrays of a library of new macrocycles known as rapafucins, which were inspired by the natural product rapamycin, we screened for new inhibitors of GLUT1. We identified multiple hits from the rapafucin 3D microarray and confirmed one hit as a bona fide GLUT1 ligand, which we named rapaglutin A (RgA). We demonstrate that RgA is a potent inhibitor of GLUT1 as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…15 Finally, FKBPs are the key enabling adaptors for the clinically approved immunosuppressants FK506 and rapamycin as well as for several recently identied molecular glues. [16][17][18][19][20][21][22] Previously, we developed bicyclic [4.3.1] sulfonamides, [23][24][25][26][27] which mimic the core of the natural products FK506 and rapamycin, retain the anti-infective 23 and BMP-stimulating properties 6,10 of these natural products, but lack their immunosuppressive properties. However, the shallow FKBP binding site generally makes the development of ligands with drug-like properties challenging.…”
Section: Introductionmentioning
confidence: 99%
“…15 Finally, FKBPs are the key enabling adaptors for the clinically approved immunosuppressants FK506 and rapamycin as well as for several recently identied molecular glues. [16][17][18][19][20][21][22] Previously, we developed bicyclic [4.3.1] sulfonamides, [23][24][25][26][27] which mimic the core of the natural products FK506 and rapamycin, retain the anti-infective 23 and BMP-stimulating properties 6,10 of these natural products, but lack their immunosuppressive properties. However, the shallow FKBP binding site generally makes the development of ligands with drug-like properties challenging.…”
Section: Introductionmentioning
confidence: 99%
“…30 In addition, previous experiments have shown that some GLUTs transport inhibitors have shown good effects in inhibiting tumor growth in mice, making GLUTs a potential target for tumor therapy. 31 Summary, this recent study demonstrates that TCF4 downregulation sensitizes melanoma cells to Vemurafenib through inhibiting GLUT3-mediated glycolysis. These findings support TCF4 as an oncogene and provide new mechanism by which TCF4 confers chemotherapy resistance in melanoma.…”
Section: Discussionmentioning
confidence: 88%
“…There is also evidence that apoptosis of tumor cells is directly induced by reducing the levels of ATP. 35 Guo et al 66 have confirmed that rapaglutin A inhibits glucose uptake, reduces ATP synthesis, and induces apoptosis. Our data showed that PFK15 in A-RAMP inhibited ATP and MMP and promoted ROS production, inducing a strong effect on tumor apoptosis both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%